2013
DOI: 10.1155/2013/140467
|View full text |Cite
|
Sign up to set email alerts
|

Control Group Design: Enhancing Rigor in Research of Mind-Body Therapies for Depression

Abstract: Although a growing body of research suggests that mind-body therapies may be appropriate to integrate into the treatment of depression, studies consistently lack methodological sophistication particularly in the area of control groups. In order to better understand the relationship between control group selection and methodological rigor, we provide a brief review of the literature on control group design in yoga and tai chi studies for depression, and we discuss challenges we have faced in the design of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 36 publications
1
129
0
Order By: Relevance
“…There may have been little room for improvement in participants' fruit intake and possibly a need for greater emphasis in the WFS lesson on the promotion of vegetable intake. A strength of using an active control group in the WFS trial was the ability to control for attention, time, and expectations regarding the lesson received; a disadvantage, however, was that it may have been more difficult to detect an intervention effect [29]. It has been suggested that providing individuals with any active intervention content is likely to lead to some change in behavior [30].…”
Section: Discussionmentioning
confidence: 99%
“…There may have been little room for improvement in participants' fruit intake and possibly a need for greater emphasis in the WFS lesson on the promotion of vegetable intake. A strength of using an active control group in the WFS trial was the ability to control for attention, time, and expectations regarding the lesson received; a disadvantage, however, was that it may have been more difficult to detect an intervention effect [29]. It has been suggested that providing individuals with any active intervention content is likely to lead to some change in behavior [30].…”
Section: Discussionmentioning
confidence: 99%
“…This group of scientific control enables the experimental study of one variable at a time, and it is an essential part of the scientific method. In a controlled experiment, two identical experiments are carried out: in one of them, the treatment or tested factor (experimental group) is applied; whereas in the other group (control), the tested factor is not applied (Kinser & Robins, 2013). …”
Section: Sample Structure and Sizementioning
confidence: 99%
“…Use of an active control group is preferred. 74,75 Hence, future studies should include an active control design to fully evaluate benefits of ACT. Due to the small sample size we did not consider significance testing.…”
Section: Limitationsmentioning
confidence: 99%